2022
DOI: 10.1177/08944393211071068
|View full text |Cite
|
Sign up to set email alerts
|

A Novel iOS Data Donation Approach: Automatic Processing, Compliance, and Reactivity in a Longitudinal Study

Abstract: For social scientists who are interested in understanding smartphone-usage patterns, as well as the causes and effects of smartphone use, it is crucial to get accurate estimates of smartphone and app usage. For this reason, we present a novel data donation approach based on screen video recordings of information provided by the iOS Battery Section. In this paper, we describe the Python script that can be used to process the data automatically. Moreover, we tested accuracy of the script, feasibility of the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Participating in a data donation study is an active task that requires a basic level of digital literacy (Baumgartner, 2022), and therefore can place more burden on people with lower technical skills. Self-assessed smartphone skills in earlier studies, however, show contradictory results: Wenz et al (2019) and Ohme et al (2021)found that participants with higher phone skills were more willing to participate, but in the study of Keusch et al (2019) and Struminskaya et al (2020) these skills were not associated with the willingness to participate.…”
Section: Respondents' Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participating in a data donation study is an active task that requires a basic level of digital literacy (Baumgartner, 2022), and therefore can place more burden on people with lower technical skills. Self-assessed smartphone skills in earlier studies, however, show contradictory results: Wenz et al (2019) and Ohme et al (2021)found that participants with higher phone skills were more willing to participate, but in the study of Keusch et al (2019) and Struminskaya et al (2020) these skills were not associated with the willingness to participate.…”
Section: Respondents' Characteristicsmentioning
confidence: 99%
“…Nevertheless, data donation is more burdensome compared to other, passive modes of data sharing (Keusch et al, 2019;Silber et al, 2022), since participants are required to actively download their data or even install a software for processing purposes, and then share it with the researchers. While data donation holds great promise to study online human behavior and some recent studies reported promising results (Baumgartner et al, 2022;Breuer et al, 2022;Kmetty & Bozsonyi, 2022;Kmetty & Németh, 2022), little is known about how to best optimize such approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, we suggest using digital methods to untangle the ever-tighter nexus of communication and participation among young citizens. Digital methods based on longitudinal, high frequency measurements (e.g., Beyens et al 2021), data donations (e.g., Baumgartner et al 2022), or digital trace data (Mangold et al 2021) may offer great starting points to understand young generations’ norms, attitudes, and behaviour. Yet, such methods are mostly used in fields other than political youth studies, such as entertainment or well-being.…”
Section: What Is Next For Political Youth and Media Studies?mentioning
confidence: 99%
“…The proliferation of digital trace data (Baumgartner et al, 2022;Choi, 2020;Jungherr et al, 2017;Kreuter et al, 2020;Revilla et al, 2017) has led to a "Big Data" revolution (Chen & Quan-Haase, 2020;Christ et al, 2021;Eck et al, 2021;Gil de Zuniga & Diehl, 2017;Wells & Thorson, 2017). Now, social scientists can explore new questions in human behavior that were difficult or impossible to study in the past.…”
Section: Introductionmentioning
confidence: 99%